Economic/ecological tradeoffs among ecosystem services and biodiversity conservation - Hussain, Abul Maala Tanvir; Tschirhart, John (© 2013 Elsevier B.V., 2016)
This article was published in Ecological Economics [© 2013 Elsevier B.V.] and the definite version is available at: http://www.sciencedirect.com/science/article/pii/S0921800913001523